Natural Sounding Standard Malay Speech Synthesis Based On UTMK EBMT Architecture System - Tiun, Sabrina (2011)
In this research work, we make natural sounding speech synthesis as the main goal. This goal was chosen following the type of demanded speech synthesis application systems by the industrial market; the limited-domain speech synthesis application systems. The limited-domain speech synthesis application system has restricted number of vocabularies (less flexible) but requires a highly natural sounding of speech synthesis. Based on the evolution of speech synthesis technique, one can conclude that using natural speech units without applying any signal processing is the technique to produce the most natural sounding of synthetic speech.